Perancangan Kampanye Wisata Kawasan Riung, Flores, NTT Untuk Wisatawan Asing - Gisela Anindita (AKSA: Jurnal Desain Komunikasi Visual, 2018)
Indonesia has extraordinary natural beauty. The natural beauty with a mixture of tropical climate makes Indonesia has its own exotic expression in the eyes of foreign tourists. Unfortunately, only a few natural attractions that are considered by foreign tourists, and these places are increasingly crowded and not considered the preservation of nature. This campaign offers a new natural tourist destination in the eastern part of Indonesia, namely an area on the island of Flores called Riung. A coastal coastal area that is calm and still maintained by its natural beauty. By applying the concept of Ecotourism, this campaign invites foreign tourists to mingle with the lives of the peaceful Riung people while enjoying the exotic natural beauty of Riung.